Profile of a ‘good’ foreign language teacher in a high school: Research report - Mihułka, Krystyna; Chojnacka-Gärtner, Joanna (Glottodidactica, 2019)
The aim of this article is to present the profile of a ‘good’ foreign language teacher, which has been created on the basis of the comments made by about 230 students of modern languages at Polish institutions of higher education (colleges and universities) in two voivodeships of Poland, namely Podkarpackie Voivodeship and Wielkopolska Voivodeship. In this image, teacher personality traits, the majority of which are regarded as values not only in professional life (e.g. in the teaching profession), but also in personal life, have ranked the highest. Personality traits have overshadowed the other two groups of qualities, which foreign language teachers are also equipped with, i.e. didactic and glottodidactic ones. This study is part of a larger research project covering all types of schools in Poland (from primary schools, through middle and secondary schools, to colleges and universities)